2012
DOI: 10.1097/aog.0b013e318255060c
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymph Node Ratio and Clinicopathologic Parameters in Patients Diagnosed With Stage IIIC Endometrial Cancer

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 21 publications
3
48
0
Order By: Relevance
“…7 Survival results are comparable to other series of mixed-histology, lymph nodeYpositive endometrial cancer, 3,7Y16 and the percentage of patients with positive lymph nodes was consistent with other studies. 7,9,10 Reports have been somewhat inconsistent in determining which factors predict survival. In this study, high-grade tumors are associated with poorer OS, which is consistent with the majority of reports, 3,9,10,13 but not in all.…”
Section: Discussionsupporting
confidence: 90%
“…7 Survival results are comparable to other series of mixed-histology, lymph nodeYpositive endometrial cancer, 3,7Y16 and the percentage of patients with positive lymph nodes was consistent with other studies. 7,9,10 Reports have been somewhat inconsistent in determining which factors predict survival. In this study, high-grade tumors are associated with poorer OS, which is consistent with the majority of reports, 3,9,10,13 but not in all.…”
Section: Discussionsupporting
confidence: 90%
“…12Y15 However, the site of lymphatic involvement was reported to be unrelated to survival in stage IIIC endometrial cancer. 16,17 In this study, 3-year DSS for stage IIIC1 and IIIC2 disease were similar (88% vs 80%, respectively). Nevertheless, the difference between these 2 groups had a tendency to be significant for 3-year PFS (P = 0.094) in our study.…”
Section: Discussionsupporting
confidence: 47%
“…Previous multi-center retrospective studies in endometrial cancer have found LNR to be associated with worse progression-free and overall survival. [1112] A significant correlation between LNR and survival has also been seen in cervical cancer in single-institution retrospective studies, however, across all stage distributions and in patients receiving neoadjuvant chemotherapy prior to surgery. [1315]…”
Section: Introductionmentioning
confidence: 99%